Adolescent subthreshold‐depression and anxiety: psychopathology, functional impairment and increased suicide risk. (18th January 2013) - Balázs, Judit; Miklósi, Mónika; Keresztény, Ágnes; Hoven, Christina W.; Carli, Vladimir; Wasserman, Camilla; Apter, Alan; Bobes, Julio; Brunner, Romuald; Cosman, Doina; Cotter, Pádraig; Haring, Christian; et al.
<x xml:space="preserve">Abstract</x> Background: Subthreshold‐depression and anxiety have been associated with significant impairments in adults. This study investigates the characteristics of adolescent subthreshold‐depression and anxiety with a focus on suicidality, using both categorical and dimensional diagnostic models. Methods: Data were drawn from the Saving and Empowering Young Lives in Europe (SEYLE) study, comprising 12, 395 adolescents from 11 countries. Based on self‐report, including Beck Depression Inventory‐II (BDI‐II), Zung Self‐Rating Anxiety Scale (SAS), Strengths and Difficulties Questionnaire (SDQ) and Paykel Suicide Scale (PSS) were administered to students. Based on BDI‐II, adolescents were divided into three groups: nondepressed, subthreshold‐depressed and depressed; based on the SAS, they were divided into nonanxiety, subthreshold‐anxiety and anxiety groups. Analyses of Covariance were conducted on SDQ scores to explore psychopathology of the defined groups. Logistic regression analyses were conducted to explore the relationships between functional impairments, suicidality and subthreshold and full syndromes. Results: Thirty‐two percent of the adolescents were subthreshold‐anxious and 5.8% anxious, 29.2% subthreshold‐depressed and 10.5% depressed, with high comorbidity. Mean scores of SDQ of subthreshold‐depressed/anxious were significantly higher than the mean scores of the nondepressed/nonanxious groups and significantly lower than those of the depressed/anxious groups. Both subthreshold and threshold‐anxiety and depression were related to functional impairment and suicidality. Conclusions: Subthreshold‐depression and subthreshold‐anxiety are associated with an increased burden of disease and suicide risk. These results highlight the importance of early identification of adolescent subthreshold‐depression and anxiety to minimize suicide. Incorporating these subthreshold disorders into a diagnosis could provide a bridge between categorical and dimensional diagnostic models.